2009
DOI: 10.1177/0961203309347921
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large B-cell lymphoma of the central nervous system in mycophenolate mofetil-treated patients with systemic lupus erythematosus

Abstract: Patients with systemic lupus erythematosus (SLE) are susceptible to the development of lymphoproliferative disorders and postulated causes include intrinsic defects in immune surveillance and iatrogenic administration of immunosuppressants. Since the introduction of mycophenolate mofetil (MMF) to the immunosuppressive regimen for the management of post-organ transplantation, there have been reports of primary lymphoma of the central nervous system (PCNSL). MMF has been widely used to treat active SLE patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 11 publications
2
20
0
4
Order By: Relevance
“…All case studies including ours were treated long term with mycophenolate indicating that prolonged immunosuppression may be one of the prerequisites for PCNSL development [23, 3638]. All reported patients had at least 5 years of autoimmune disease.…”
Section: Discussionmentioning
confidence: 95%
“…All case studies including ours were treated long term with mycophenolate indicating that prolonged immunosuppression may be one of the prerequisites for PCNSL development [23, 3638]. All reported patients had at least 5 years of autoimmune disease.…”
Section: Discussionmentioning
confidence: 95%
“…La survenue d'un lymphome du SNC chez un patient lupique reste exceptionnelle puisque seuls 14 cas ont été publiés à ce jour à notre connaissance [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Onze cas sont résumés dans le tableau, un cas n'étant pas renseigné [21], le diagnostic de LED étant incertain dans un second cas [25] et le lymphome étant survenu chez une patiente suivie pour un LES ayant eu une transplantation rénale [26], ce qui peut être un facteur confondant.…”
Section: Discussionunclassified
“…Il s'agit de femmes d'âge moyen (42,5 ans en médiane), présentant des signes neurologiques focaux, pour lesquelles le diagnostic de lymphome du SNC est évoqué sur l'aspect nodulaire des lésions avec rehaussement périphérique lors de l'injection de produit de contraste à l'imagerie. Une ponction lombaire n'a été réalisée que chez 2 patientes dont l'une retrouvait une méningite lymphocytaire hyperprotéinora-chique [15,23]. Le diagnostic de lymphome cérébral primitif a été obtenu par biopsie stéréotaxique (7 cas), et lors de l'exérèse chirurgicale de la lésion (1 cas) (Tableau 1).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Fortunately, none of the subjects in our cohort became pregnant and we advise practitioners to counsel female patients accordingly. A very rare but serious complication of MMF therapy, mentioned in a report of B cell lymphomas in three patients with SLE, was the occurrence of primary central nervous system lymphoma (PCNSL) in a single patient with dermatomyositis treated with MMF and methotrexate, which spontaneously resolved with discontinuation of both drugs (40). It is clear that because of the lack of controlled trials in patients with myositis, the role of MMF remains to be confirmed.…”
Section: Discussionmentioning
confidence: 99%